Analisis Bahaya Gempa Bumi Berdasarkan Nilai Peak Ground Acceleration (PGA) Menggunakan Metode Probabilistic Seismic Hazard Analysis (PSHA) di Wilayah Bali dan Nusa Tenggara - Muhammad Hafeezul; Yudha Styawan; Rizki Wulandari (Mataram University, 2026)
The Bali, West Nusa Tenggara (NTB), and East Nusa Tenggara (NTT) regions are located within an active tectonic zone influenced by the transition subduction of the Sunda–Banda arc and the presence of surrounding active faults, resulting in a high potential for earthquake hazards. This study was conducted to evaluate seismic hazard through the estimation of Peak Ground Acceleration (PGA) using the Probabilistic Seismic Hazard Analysis (PSHA) method. The analysis is based on an earthquake catalog covering the period 1964–2024 and considers various seismic sources, including shallow background, deep background, active faults, and megathrust sources. Earthquake occurrence models for fault and subduction sources were represented using a truncated exponential model. Ground motion predictions were calculated using several Ground Motion Prediction Equations (GMPEs), which were combined through a logic tree approach. The calculations were performed at bedrock conditions with a Vₛ30 value of 760 m/s, for exceedance probabilities of 10% and 2% within a 50-year period. The results indicate that PGA values for a 10% probability of exceedance range from 0.30 to 1.18 g, while those for a 2% probability of exceedance range from 0.62 to 1.75 g. High PGA values are distributed in the southern and eastern regions, which are adjacent to megathrust segments and active faults with high slip rates, whereas the northern regions exhibit lower PGA values. These results are important for public awareness in earthquake disaster mitigation efforts and for earthquake-resistant building planning.